KNOWLEDGE OF PATIENTS WITH HYPERTENSION ABOUT THEIR TREATMENT (Fiep Bulletin - online, 2011)
Hypertension is a major risk factor for death among non-communicable diseases, showing direct relationship with cardiovascular risk. However, despite progress in prevention, diagnosis and treatment is still an important public health problem.Investigate the knowledge of patients with hypertension on the treatment adopted for the same. Cross-sectional study in which the sample included 72 hypertensive patients. Data collection was through interviews, the Basic Health Unit José Leite Rolim Cajazeiras / CP, via structured interview. The data were analyzed quantitatively the light of relevant literature. The sample was characterized by a good percentage of hypertensive patients aged under 40 (34.71%), nearly half of the sample has a permanent relationship (49.99%), a large percentage of the level of schooling for high school and most (48.86%), the vast majority have incomes of up to two minimum wages (83.32%). The vast majority (75%) know the real meaning of hypertension, attributing concepts from their values and beliefs, a small minority (18%) found the disease in a routine visit and the treatment they are best known for the drug anddecrease in diet (100%) of the sample, with a frequency (22.78%) as the measures adopted was the least valued physical activity (8.84%). (22.48%) said the main difficulty following the treatment and medication adjustment as easily purchase the medication through the clinic (48%) Many patients reported not have doubts as to the treatment (45.26%). It was found that hypertensive patients do not know for sure what is hypertension, but they have a good knowledge about their treatment, this is evidenced by the few issues that arose during the interviews. According to the findings have noticed the need for educational measures seek to influence, really, the behavior of hypertensive patients, the effect of changes in habits and lifestyle.Besides the creation of groups of hypertensive patients to doubts and difficulties are discussed, and the exchange of experience make possible the awakening of a better awareness of the disease.
Keywords: Hypertension; Questions; Treatment